From Monomodal to Multimodal Corpus: Grounds, Studies, and Agenda - Argina, Ade Windiana; Prasetyo, Ilham Agung; Setiawan, Rozi (Syntax Literate, 2026)
This article provides a comprehensive literature review on the emergence and development of multimodal corpus pragmatics, a field that integrates multimodality, pragmatic theory, and corpus-based approaches. Technological advancement has shifted linguistic inquiry from traditional monomodal corpora toward multimodal data that capture verbal and non-verbal semiotic resources such as gesture, facial expression, prosody, and embodied actions. Drawing from theoretical contributions (Huang, Gu, Payrato, Kendon, Kress & van Leeuwen) and empirical studies across film, advertising, documentary, and product presentation contexts, this review highlights how multimodal corpora enrich the analysis of meaning-making, speech act performance, implicature recovery, and identity construction. The analysis discusses four major themes: (1) the conceptual grounds for transitioning from monomodal to multimodal pragmatic corpora, (2) theoretical and empirical findings demonstrating the methodological advantages of multimodal pragmatics, (3) proposed units of analysis for multimodal annotation, and (4) future agendas including methodological challenges, tool development, and interdisciplinary expansion. The review concludes that multimodal corpus pragmatics offers a more comprehensive representation of human communication while presenting substantial analytical and technical challenges. Its pedagogical implications suggest the relevance of integrating multimodal pragmatic awareness into language teaching to enhance learners’ communicative competence.